Does freezing a defined benefit pension plan affect firm risk? - Choy, Helen; Lin, Juichia; Officer, Micah S. (Journal of Accounting and Economics, 2014)
This paper examines the impact of a defined benefit (DB) pension plan freeze on the sponsoring firm's risk and risk-taking activities. Using a sample of firms declaring a hard freeze on their DB plans between 2002 and 2007, we observe an increase in total risk (proxied by the standard deviation of EBITDA and asset beta), equity risk (standard deviation of returns), and credit risk following a DB-plan freeze. The increase in credit risk is reflected in a decline in credit ratings and an increase in bond yields for freezing firms. When we examine investment strategies, we observe a shift in investment from capital expenditures before the freeze to more-risky R&D projects after the freeze, and an increase in leverage. These strategies (increased focus on R&D and higher leverage) increase the operating and financial risk the firm faces. Overall, we observe an increase in risk-taking following DB plan freezes, consistent with theories that DB plans act as “inside debt” that aligns managers’ interests with bondholders’.